2008
DOI: 10.1051/0004-6361:20078961
|View full text |Cite
|
Sign up to set email alerts
|

The long-period Galactic Cepheid RS Puppis

Abstract: Context. The bright southern Cepheid RS Pup is surrounded by a circumstellar nebula reflecting the light from the central star. The propagation of the light variations from the Cepheid inside the dusty nebula creates spectacular light echoes that can be observed up to large distances from the star itself. This phenomenon is currently unique in this class of stars. Aims. For this relatively distant star, the trigonometric parallax available from Hipparcos has a low accuracy. A careful observation of the light e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
5
46
0
Order By: Relevance
“…Before these observations, only one Cepheid was known with certainty to be surrounded by a circumstellar envelope (CSE), RS Pup. This large nebula (≈2 ) scatters the light from the central star, and hosts one of the most striking examples of light echoes known to date (Kervella et al 2008). Another Cepheid, SU Cas, is close to a nebula, but the physical association is uncertain.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Before these observations, only one Cepheid was known with certainty to be surrounded by a circumstellar envelope (CSE), RS Pup. This large nebula (≈2 ) scatters the light from the central star, and hosts one of the most striking examples of light echoes known to date (Kervella et al 2008). Another Cepheid, SU Cas, is close to a nebula, but the physical association is uncertain.…”
Section: Introductionmentioning
confidence: 73%
“…3 shows the circumstellar nebula of RS Pup in the V band, from observations with the NTT/EMMI instrument by Kervella et al (2008). In this wavelength range, we observe the scattered light from the central star.…”
Section: Rs Pup Imagesmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous projects have shown that maintenance is very costly when authors use HTML Kervella et al 2008); Right: understanding a scheme or an image (optical scheme of the HARPS spectrometer dedicated to very high precision radial velocity measurement, Pepe et al 2003). to create courses : the mix of content and presentation markup makes separate changes in either of these areas much harder. The use of CSS can help alleviate these problems with the definition of classes for document parts, but XML goes much further.…”
Section: Technical Specificationsmentioning
confidence: 99%